Electoral Dispute Resolution in Ghana since 1992: An Assessment of the Role of the Judiciary Arm of State (Journal of Advanced Research in Social Sciences, 2022)
Since becoming a constitutional democracy in 1993, many electoral disputes have arisen in Ghana following elections, with both state and non-state agencies playing key roles in the resolution of these disputes at the levels of general elections, bye-elections, assembly elections, inter alia. The focus of this paper, however, is an examination of the effectiveness of the electoral dispute resolution role of the judiciary arm of state, as mandated under Articles 64(1) and 99(1) of the 1992 Fourth Republican Ghanaian Constitution. Additionally, this paper seeks to identify the underlining causes of electoral disputes in Ghana, as well as, assess the potency of the electoral structure of the country. The study adapted the qualitative research approach in gathering data from 120 respondents that were purposively selected across 16 administrative regions in the country, in addition to the use of secondary and tertiary data. The study argues that the Apex Court namely, the Supreme Court of Ghana has been largely effective in terms of electoral disputes resolution, with a bigger chunk of the credit, however, going to the citizens who are law abiding and peace loving. Furthermore, actions and inactions of the Electoral Commission (EC) as well as political parties in Ghana, have gravely contributed to the spate of electoral disputes in Ghana. Against the backdrop of these findings, it is recommended amongst others that, judges of the Superior Court of Judicature dispense justice fairly and impartially and devoid of material and political underpinnings; whilst electoral officials are urged to play the role of impartial umpires throughout election processes. The researcher argues further that, should stakeholders carefully implement recommendations of this study; the confidence of the electorate in the Ghanaian electoral system will soar once more.